(untitled) (Research, Society and Development, 2021)
Deforestation in the Legal Amazon has increasingly occupied a prominent place in public discussions. The state of Pará is one of the states that most illegally suppresses vegetation cover. This article aims to find out how the civil police of the state of Pará has been working to combat crimes against flora. The research took a qualitative and quantitative approach. Statistical data made available by the Secretariat of Intelligence and Criminal Analysis - SIAC on police reports and procedures put in place to investigate crimes against flora were used, as well as data from the main official platforms for monitoring deforestation in Brazil. The time frame was the period between January 2017 and January 2020. An interview was also conducted with the head of the police station for the repression of crimes against flora. The results showed that crimes against flora in Pará are underreported and that the civil police face serious obstacles to instructing police investigations due to the scarcity of material and human resources in addition to the economic and political power of most of those investigated. The research concludes that for an effective confrontation of crimes against flora, it is necessary to equip the judicial police, educate and raise awareness among the population about their role in informing the authorities about environmental devastation.